2010
DOI: 10.5141/jefb.2010.33.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Control of an invasive alien species, Ambrosia trifida with restoration by introducing willows as a typical riparian vegetation

Abstract: We evaluated the restoration effect by introducing willows as a means of controlling invasions of giant ragweed (Ambrosia trifida L.) on a riparian site. Our preliminary survey demonstrated that a problematic exotic species, giant ragweed and the representative riparian species, Salix koreensis are in competitive exclusive relationship. We planted willows at 1 m intervals on the bank of the Dongmun stream at Munsan, Paju, in Central Western Korea as an experimental restoration practice. We installed two 50 m ⅹ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Only one study has reported the use of native plant restoration to suppress A. trifida invasion (Lee et al 2010). The introduction of willow (Salix sp.)…”
Section: Discussionmentioning
confidence: 99%
“…Only one study has reported the use of native plant restoration to suppress A. trifida invasion (Lee et al 2010). The introduction of willow (Salix sp.)…”
Section: Discussionmentioning
confidence: 99%
“…Giant ragweed has remained largely restricted to ruderal habitats, which might be one of the reasons for its slow spread in Central and Eastern Europe (Follak et al, 2013). Outside of this region, A. trifida occurs in several (semi-) natural habitats (Lee et al, 2010). As for A. artemisiifolia and I. xanthifolia, they have both undergone a habitat shift and expansion during their invasion, which may have contributed to their more extensive colonization of Central and Eastern Europe (Follak et al, 2013;Essl et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, A. trifida can be found predominantly along riverbanks, mostly in disturbed locations (artificial banks, bridges and quarries) but also in the riverine vegetation (Miyawaki & Washitani, 2004). In South Korea, it occurs in the riparian systems of streams and rivers and around agricultural fields, on road edges and landfill sites and, recently, it has also invaded forest edges and interiors (Lee et al , 2010). In Japan and South Korea, A. trifida grows also in semi‐natural areas (Miyawaki & Washitani, 2004; Lee et al .…”
Section: Biology and Ecologymentioning
confidence: 99%
“…In Japan and South Korea, A. trifida grows also in semi‐natural areas (Miyawaki & Washitani, 2004; Lee et al . , 2010).…”
Section: Biology and Ecologymentioning
confidence: 99%
See 1 more Smart Citation